PEMBERDAYAAN MASYARAKAT UNTUK PENYEHATAN LINGKUNGAN SEBAGAI UPAYA PENCEGAHAN RISIKO STUNTING - Tanti Asrianti; Muhammad Sultan; Sekar Arum Mulyasyarif; Siti Miftahul Jannah; Natasya Cicilia Suwuh; Wahyu Tri Prayogi; Andini Sarah Rahmayani; Annisa Delillah Priyanti; Sendila Ernesy Asari; Shenny Ratna Damayanti (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2023)
Stunting is a public health problem with high prevalence globally and nationally. The prevalence of stunting in Indonesia in 2021 was 24,4%. One of associated risk factors is environment, including waste management. Based on the results of observation and survey at Handil Bakti, Palaran District, Samarinda City, it was found that more than 37% of household did not manage their waste properly. Therefore, through the community service program, audio-visual media in the form of educational video are made by involving the local community to increase knowledge about how to manage household waste and community participation in the waste bank. It showed that the Video indirectly increase community involvement in the utilization of waste bank which were previously only managed by waste bank administrators. Video access and the language used is easily accessible to all people so it can ensure program sustainability.